The feminist standpoint theory reader: Intellectual and political controversies - Harding, Sandra G. (Routledge, 2004)
Leading feminist scholar and one of the founders of Standpoint Theory, Sandra Harding brings together the biggest names in the field--Dorothy Smith, Donna Haraway, Patricia Hill Collins, Nancy Hartsock and Hilary Rose--to not only showcase the most influential essays on the topic but to also highlight subsequent interrogations and developments of these approaches from a wide variety of disciplines and intellectual and political positions.
Keywords: approches et analyses; cours; discipline; fem1000; har4600; incontournable; interdisciplinarité; point de vue situé; pol4212; premier cycle; privilèges; ressource en ligne; sciences humaines; systèmes d'oppressions; épistémologie